Frequency preserving coherent opto-acoustic storage - Stiller, Birgit; Merklein, Moritz; Poulton, Christopher; Vu, Khu; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (Optics InfoBase Conference Papers, 2018)
We experimentally demonstrate that the coherence of Brillouin-based storage is not affected by simultaneous storage on another frequency channel because of the accumulated phase mismatch over the length of the spatially extended acoustic phonon.
CRIS-Team Scopus Importer:2021-06-29